Factors associated with pap smear and visual inspection alterations and oncogenic high-risk DNA-HPV Detection in women ofone basic health unit from Campinas - Gontijo, Renata C.; Derchain, Sophie FM; Ortiz, Rodrigo T.; Guarisi, Renata; Sarian, Luiz Otávio Z.; Bragança, Joana F.; Zeferino, Luiz Carlos (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Objective: To evaluate assoei a ted factors with Pap smear and visual inspection with acetic acid (VIA) alterations and DNA-HPV detection in women attended in a health unit from Campinas. Subjects and methods: Cross transversal study with 733 women evalualed in one basic hcalth unit. All of them had material collected for Pap smear and VIA was performed in 676 women. Hybrid capture II (HCII) for DNA-HPV detection was collected in 218 women. To asses the relation between groups. odds ratio werc calculated with 95% confidence interval. Results: The Pap smear results was normal in 92,2% of women and was inadequate in 1,4%. Atypical cells were found in 47 (6,4%) women (30 ASCUS. 13 LSIL. three HS1L and one glandular atypia). Living without a sexual partner and having five or more sexual partners were associated with abnormal Pap smear rcsult. VIA was suggestive of intra-epithelial lesions in 16 (2,4%) women. Among the 218 women that had DNA-HPV analysis, 20.6% were positive for oncogenic high-risk virus. The factor significantly associated with DNA-HPV positivity was smoking. Low concordance was observed among the different tesls. Conclusion: In this population. HC II had the highest positivity frequency followed by Pap smear and VIA. Smoking showed association with DNA-HPV positivity. and living without a partner and having more than 5 sexual partners were significantly associated with abnormal Pap smear resull.